(untitled) (European Bison Conservation Newsletter, 2012)
The present state of the population of the European bison (Bison bonasus) “Osipovichskaya” (regarded as the reserve of gene pool for this species), natural food supply and the level of supplemental feeding are reviewed. Demonstrated are methods used for the improvement of food supply available for the bison. Numbers of “Osipovichskaya” population of European bison increased from 15 to 186 individuals (by 12.4 times) and exceeded the level considered as optimal (120–130 individuals). Reported are main parameters of “Osipovichskaya” population and indicated are reasons of its fast growth. Explained is the necessity and methods for the extension of the area of feeding plots that provide a significant of spring, summer and autum diet of European bison there.